A comparison of electronic and paper-based clinical skills assessment: Systematic review. (3rd October 2019) - Phillips, Anna C.; Mackintosh, Shylie Fordyce; Gibbs, Carole; Ng, Leo; Fryer, Caroline Elizabeth
Abstract: Introduction: The aim of this systematic review was to compare the effectiveness of electronic recording with paper-based recording of clinical skills assessments for entry-level health professional students. Methods: A comprehensive database search was undertaken using AMED, CINAHL, CENTRAL, EMBASE, Medline, PsycINFO, Scopus, and Web of Science on 12–16 June 2017, and updated 9 April 2018. Studies investigating electronic and paper-based recordings of clinical skills assessments of students in entry-level health professional programs were eligible for inclusion. Two independent researchers completed screening of studies for inclusion, quality assessments, and data extraction, with discrepancies resolved by consensus. Quality assessment was performed using the Critical Appraisal Skills Program Diagnostic checklist. Results: From 2264 studies identified, five observational cohort studies were included. Published between 2006 and 2016, included studies investigated electronic and paper examinations of clinical skills assessments of students from medical, dentistry, and physical therapy programs. Electronic assessments were reported to be more time efficient than paper-based assessments with an added advantage of no missing data. Quality and quantity of quantitative and qualitative student feedback increased with electronic assessment compared to paper-based assessments. Conclusions: Electronic assessments were used successfully across a range of health professional programs, take significantly less time to complete and provide higher quality feedback to students. Future studies are needed with more robust psychometric testing and cost-effective analysis to inform the increasing uptake of electronic assessment tools in health professional training.